2016
DOI: 10.1101/096024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Noninvasive Prenatal Screening at Low Fetal Fraction: Comparing Whole-Genome Sequencing and Single-Nucleotide Polymorphism Methods

Abstract: CONFLICT OF INTERESTS:All authors other than YY are employees of Counsyl Inc., a company that performs noninvasive prenatal screening. YY is a clinical expert panel member for Illumina Inc., a company that performs noninvasive prenatal screening, and a consultant for Teva Pharmaceuticals, a local distributor of noninvasive prenatal 30 screening. Abstract 60Objective Performance of noninvasive prenatal screening (NIPS) methodologies when applied to low fetal fraction samples is not well established. The single-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…The literature is replete with reports and professional society statements expressing concern about low-FF samples. 8,38,39 Many publications have explored and debated the merits of different approaches to handling low-FF samples: optimizing NIPS algorithms to issue confident results at low FF, 9 failing such samples entirely, or pursuing mitigation strategies for failed low-FF samples, such as sequential redraw 40,41 and FF-based risk scores. 42,43 However, consensus has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature is replete with reports and professional society statements expressing concern about low-FF samples. 8,38,39 Many publications have explored and debated the merits of different approaches to handling low-FF samples: optimizing NIPS algorithms to issue confident results at low FF, 9 failing such samples entirely, or pursuing mitigation strategies for failed low-FF samples, such as sequential redraw 40,41 and FF-based risk scores. 42,43 However, consensus has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Because the molecular and bioinformatic implementations of NIPS have evolved, diversified, and generally improved over time, sensitivity at progressively lower FF levels is platform-and laboratorydependent. 6,8 Indeed, a recently published clinical experience study demonstrated that a customized whole-genome sequencing (WGS)-based NIPS, which does not fail low-FF samples, can have comparable accuracy at high FF and low FF for the common aneuploidies on chromosomes 13, 18, and 21. 9 Though the common aneuploidies have long been the main focus of NIPS because of their frequency and highly penetrant phenotype, clinically actionable chromosomal anomalies span a range of sizes and can occur anywhere in the genome.…”
Section: Introductionmentioning
confidence: 99%
“…The literature is replete with reports and professional-society statements expressing concern about low-FF samples. 8,38,39 Many publications have explored and debated the merits of different approaches to handling low-FF samples: optimizing NIPS algorithms to issue confident results at low FF, 9 failing such samples entirely, 40 or pursuing mitigation strategies for failed low-FF samples, such as sequential redraw 41,42 and fetal-fraction-based risk scores. 43,44 However, consensus has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Because the molecular and bioinformatic implementations of NIPS have evolved, diversified, and generally improved over time, sensitivity at progressively lower FF levels is platform-and laboratory-dependent. 6,8 Indeed, a recently published clinical-experience study demonstrated that a customized whole-genomesequencing (WGS)-based NIPS, which does not fail low-FF samples, can have comparable accuracy at high-FF and low-FF for the common aneuploidies on chromosomes 13, 18, and 21. 9 Though the common aneuploidies have long been the main focus of NIPS because of their frequency and highly penetrant phenotype, clinically actionable chromosomal anomalies span a range of sizes and can occur anywhere in the genome.…”
Section: Introductionmentioning
confidence: 99%
“…They have been previously thoroughly reviewed by Peng and colleagues . Several attempts to compare different FF algorithms have been published that highlight the significant variation between methods . It is now apparent that individual clinical laboratories should optimize their platform‐specific FF methods according to their lower LOD, and not rely on arbitrary FF cutoff values for quality control.…”
Section: Clinical Laboratory Aspects Of Ffmentioning
confidence: 99%